Splenic irradiation in treating warm autoimmune haemolytic anaemia. Issue 6551 (4th October 1986) - Markus, H; Forfar, J C
Abstract : An elderly man with severe congestive heart failure was noted to have a haemoglobin concentration of 87 g/l and a reticulocyte count of 13%. Direct Coombs test yielded a positive result and the serum contained a moderate amount of warm antibody (IgG class). Steroids were given, but to no avail, and the patient's condition precluded splenectomy. A course of splenic irradiation was therefore tried (midline dose 2000 cGy (rads)), and 60 days later the blood film showed similar appearances to those in patients treated successfully by splenectomy. Haemoglobin concentration subsequently rose to normal. Splenic irradiation may offer a simple treatment for resistant warm autoimmune haemolytic anaemia when splenectomy is contraindicated.